PENGARUH KEPERCAYAAN DIRI TERHADAP PROKRASTINASI AKADEMIK MAHASISWA BIMBINGAN DAN KONSELING ANGKATAN 2020 DI FKIP UKSW - Yunita Enggar Prasetyarini; Umbu Tagela (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
This study aims to determine the significance of the effect of self-confidence on academic procrastination of guidance and counseling students class of 2020 at FKIP Satya Wacana Christian University. The hypothesis put forward in this study is that there is a significant effect of self-confidence on academic procrastination of 2020 guidance and counseling students at FKIP Satya Wacana Christian University. This research is a quantitative research with comparative causal research. The subjects in this study were 48 Guidance and Counseling students class of 2020. Data collection used a questionnaire. The results of the study show the value of Sig. of 0.000 (0.000 < 0.050) and t count > t table (-) (8.990 > 2.013). Self-confidence has an Rsquare value of 0.637, which means that the contribution of the self-confidence variable to the academic procrastination variable is 63.7% and the rest (37.3%) is influenced by other factors. The regression coefficient (x) is -0.795, this means that for every 1% increase in self-confidence, the student's academic procrastination value increases by -0.795. Thus it can be concluded that self-confidence has a significant effect on the academic procrastination of guidance and counseling students class of 2020 at FKIP Satya Wacana Christian University so that the hypothesis proposed in this study is accepted.Keywords: Self-Confidence; Academic Procrastination